Cyclodextrin-enhanced 1, 4-dioxane treatment kinetics with TCE and 1, 1, 1-TCA using aqueous ozone. (March 2019) - Khan, Naima A.; Johnson, Michael D.; Kubicki, James D.; Holguin, F. Omar; Dungan, Barry; Carroll, Kenneth C.
Abstract: Enhanced reactivity of aqueous ozone (O3 ) with hydroxypropyl-β-cyclodextrin (HPβCD) and its impact on relative reactivity of O3 with contaminants were evaluated herein. Oxidation kinetics of 1, 4-dioxane, trichloroethylene (TCE), and 1, 1, 1-trichloroethane (TCA) using O3 in single and multiple contaminant systems, with and without HPβCD, were quantified. 1, 4-Dioxane decay rate constants for O3 in the presence of HPβCD increased compared to those without HPβCD. Density functional theory molecular modeling confirmed that formation of ternary complexes with HPβCD, O3, and contaminant increased reactivity by increasing reactant proximity and through additional reactivity within the HPβCD cavity. In the presence of chlorinated co-contaminants, the oxidation rate constant of 1, 4-dioxane was enhanced. Use of HPβCD enabled O3 reactivity within the HPβCD cavity and enhanced 1, 4-dioxane treatment rates without inhibition in the presence of TCE, TCA, and radical scavengers including NaCl and bicarbonate. Micro-environmental chemistry within HPβCD inclusion cavities mediated contaminant oxidation reactions with increased reaction specificity. Graphical abstract: Image 1 Highlights: O3 and 1, 4-dioxane complex within hydroxypropyl-β-cyclodextrin (HPβCD). O3 reactivity and 1, 4-dioxane removal were enhanced within HPβCD cavity. 1, 4-Dioxane removal rate constants increased with HPβCD addition. 1, 4-Dioxane removal rate constants increased with co-contaminants. 1, 4-Dioxane removal rate constants increased with salt addition.